Healthcare Access Inequity within a Social Health Insurance Setting: A Risk Faced by Indonesia’s Jaminan Kesehatan Nasional (JKN) Program - Dinar Dana Kharisma (Kementerian Perencanaan Pembangunan Nasional (Bappenas), 2020)
This paper is a literature review laying out empirical evidence of healthcare access inequity within an implementation of social health insurance (SHI) programs. The research question of this paper is: in what way, and how, inequity in healthcare access potentially happens, even if a type of SHI covers the whole, or most, of a society. This paper is mainly motivated by the implementation of Jaminan Kesehatan Nasional (JKN), an SHI program in Indonesia. Even though the program aims to create better equity in healthcare access, the existing health system and the program’s design may prevent the achievement of this goal. By laying out evidence on how healthcare access inequity in other countries remains within an SHI mechanism, this paper illuminates that JKN may face the same risk. In reviewing the papers, this study applied Goddard and Smith’s (2001) concept of healthcare access inequity in the area of availability, quality, cost, and information. The findings suggest that healthcare access inequity could happen despite the implementation of an SHI program. Four types of circumstances that might have led to healthcare access inequity include geographical disparities of health facilities; adequacy of insurance program’s reimbursement and healthcare providers’ financial motive; healthcare providers’ prejudices toward patients; and unequal personal advantages of health treatment seekers. When applied to the context of JKN implementation in Indonesia, the risks of healthcare access inequity are imminent, mostly due to the uneven concentration of health facilities, the program’s segmented tariff rates, and the socioeconomic diversity among JKN members. The findings imply that JKN members might be at risk of healthcare access inequity. While the risks are plausible, this study is limited to predicting the potential inequity within JKN, mirroring from the empirical evidence. This study signifies the need for further empirical research on this area, which will potentially inform policymakers to improve the program.